Question
upstudy study bank question image url

What if the problem asked for \( \sum_{k=3}^{5}(k-2)(k-3) \)

Ask by Morrison Barrett. in the United States
Dec 06,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

The sum \( \sum_{k=3}^{5}(k-2)(k-3) \) equals 8.

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Beyond the Answer

To solve the problem \( \sum_{k=3}^{5}(k-2)(k-3) \), first, we can evaluate the expression for each value of \( k \) from 3 to 5. For \( k=3 \), \( (k-2)(k-3) \) becomes \( (3-2)(3-3) = 1 \cdot 0 = 0 \). For \( k=4 \), it becomes \( (4-2)(4-3) = 2 \cdot 1 = 2 \). Lastly, for \( k=5 \), it is \( (5-2)(5-3) = 3 \cdot 2 = 6 \). Now sum these results: \( 0 + 2 + 6 = 8 \). Another note is that the expression \( (k-2)(k-3) \) can be represented as \( k^2 - 5k + 6 \). So, if you encountered a larger sum, it might be easier to sum the individual terms in the polynomial expression instead – sometimes breaking it down can help prevent errors in more complex calculations.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy